Mengukur Citra Carrefour BG Junction Surabaya - Erida Nursiana; Aridha Prassetya; Harsono Teguh; Diana Zuhro; Sutini Sutini (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
A retail business is a business selling products and services that have been added to meet the needs of individuals, families or other end users. Retail business in Indonesia is divided into 2 groups, namely traditional retail and modern retail. Modern retail is basically a development of traditional retail. Retail business does not always have to be done in a shop, but can also be done via telephone or internet, also called retail or non-shop retail. The characteristics of a traditional retail business are simple, the place is not too large, the goods sold are not too many type, the management or management system is still simple, does not offer shopping convenience and there is still a process of haggling over prices with traders, and the products sold are not displayed openly, so customers do not know whether the retailer has the goods they are looking for or not. Meanwhile, modern retail businesses On the contrary, it offers a spacious place, there are many types of goods sold, the management system is well managed, offers shopping convenience, the selling price is fixed (fixed price), so there is no bargaining process and there is a self-service or self-service system, as well as displays products on open shelves, so customers can see, choose, and even try products first before deciding to buy. Of all the retail companies, there is one large company that also dominates the retail business currently, namely Carrefour. Carrefour is an international supermarket group, headquartered in France. Carrefour is the second largest retail group after Wal-Mart. The first Carrefour store opened on June 3, 1957, in Annecy near an intersection